Distributed energy storage participating in power trading mechanism for power system flexibility - Cui, Dongjun; He, Jinghan; Cheng, Xiaochun; Liu, Zhao (Frontiers in Energy Research, 2023)
In the paper of the participation of multiple types of market members, such as photovoltaics, wind power, and distributed energy storage, in market-based trading, the development of new power systems hinges on strengthening the adaptability of power systems to accommodate various types of market participants and improving their flexibility. The establishment of a modern power system also faced major challenges. Such as how to achieving collaborative operation between the main grid, regional distribution networks, and distributed power generation and consumption devices, and how to improving the flexibility of grid operation, and how to increasing device utilization, and reducing operating costs. In view of above-mentioned issues, this study proposed employing the traceability and anti-tampering features of blockchain technology tackle the issue of establishing mutual trust among different types of market participants and, considering the high volatility of new energy output, studies the configuration of a flexible power system in response to output deviations resulting from day-ahead forecasting-intraday operation (DAF-IDO). A market-based trading mechanism involving multiple types of market participants has been established to smooth out the deviation in output from different types of participants, improving the economic benefits of system operation. This study has made innovative contributions as follows: First, this study employed blockchain technology to enable the participation of various types of market participants in trading activities together. Second, this study proposed a method for determining DAF-IDO energy storage action deviations to allow regional distribution networks based on distribution network operators to quantitatively calculate their energy storage supply and demand, providing crucial methodological support for their participation in market trading in the future. Third, the study developed a trading mechanism based on combinatorial auctions for multiple types of market participants, and incorporated an valley compensation mechanism into the pricing mechanism to encourage active and autonomous participation of users, while also considering the economic benefits of all parties involved. Ultimately, numerical simulations were conducted to verify the feasibility and rationality of the trading mechanism, taking into account the DAF-IDO energy storage action deviations while multiple regional networks are participating.